Analysis Of Financial Statements To Assess Performance At PT Unilever Indonesia Tbk - Putri, Alda Ayu; Hidayah, Nenden Restu (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
According to the findings of the research, it can be demonstrated that PT Unilever Indonesia Tbk is a manufacturing company that is listed on the Indonesia Stock Exchange. The ratios present in the financial statements can convey tidbits of information about the company's ability to manage its resources, fulfill short-term and long-term debt obligations, and establish strategic plans. An assessment of financial performance and analysis of financial statements is crucial, as it offers management a clear understanding of the company's status and can serve as a fundamental basis for decision-making. This analysis aids management in recognizing operational strengths and weaknesses, as well as identifying potential opportunities. this also helps to ensure the sustainability and growth of the business by delivering accurate information regarding the company’s financial health, operational performance, and potential risks.